ANALISI CAMPUR KODEDAN ALIH KODE DALAM PROSES PEMBELAJARAN BAHASA JAWA DI SMP NEGERI 1 SAMBI KABUPATEN BOYOLALI - , Syarif Hidayat ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research emphasizes on classifying kinds of code in a study case of Javanese language learning at SMP N 1 Sambi, Boyolali. This research will be completed using sociolinguistic approach. The purpose of this research is to know the occurrence of mixing code and changing code that happens in Javanese language learning process at SMP N 1 Sambi, Boyolali. The data which is used in this research is taken from oral data using observation technique directly and involves participants. As the result of the research, there were mixing code and changing code that have done by the students and the Javanese languageâ teachers at Javanese language learning process SMP N 1 Sambi, Boyolali. The form of mixing code and changing code in the Javanese language learning process are Javanese language with Indonesian language, and Javanese with English.